INDUSTRIAL MUSHROOM AS AN INNOVATIVE DIRECTION ECONOMIC ACTIVITY IN THE SPHERE OF THE APC OF THE RUSSIAN FEDERATION - A. V. Soldatenko; A. F. Razin; R. D. Nurmetov; N. L. Devochkina; O. A. Razin (Овощи России, 2018)
The article presents an analysis of the state of mushroom growing in the world as one of the leading directions of the intensive agricultural sector of the economy, analyzes and identifies areas for the future development of mushroom growing in the Russian Federation in the light of the implementation of the State program for the development of agriculture and regulation of markets of agricultural products, raw materials and food for 2013-2020. The goals, directions and expected potential of development of branch construction of new mushrooming complexes in the Russian Federation, necessity of expansion of volumes and assortment of produced valuable food crops are proved, target parameters of the software of the branch are outlined. The principles of organization of mushrooming and promising technological solutions for improving the economic efficiency of production are recommended. Measures of state support for mushroom farming are described. The advantages of intensive industrial cultivation of edible fungi in conditions of protected soil are substantiated. Key words: industrial mushroom cultivation, cultivation facilities, full production cycle, organizational and technological production system, mushroom, oyster mushroom, shiitake.